Children’s Health Care in Chuvashia Region During the Great Patriotic War of 1941–1945 - Roman S. Matveev; Valeriy Yu. Albitskiy; Tamara G. Denisova; Stella A. Sher; Melsik S. Denisov; Ludmila L. Kozyreva (Вопросы современной педиатрии, 2022)
This article presents the results of historical and medical study reflecting the state of child health care system in Chuvash Autonomous Soviet Socialist Republic during the Great Patriotic War of 1941–1945. The aim of the study is to analyze the situation regarding children’s health care during the most crucial period for our country. We have studied published and unpublished documents from the State Archive of Russian Federation, archives of Chuvash Republic, newspapers, journals, collections of scientific articles, and monographs to cover this issue. Local health authorities have significantly reorganized their work during the war years and set new tasks for protection of local and evacuated children’s health and lives. People’s Commissariat of Public Health of Chuvash Autonomous Soviet Socialist Republic has managed to prevent the reduction in the number of pediatric medical and preventive institutions, implemented their adequate staffing level, increase the efficacy of therapeutic and preventive measures, and resist infectious diseases outbreaks even under the evacuation measures, insufficient funding, and lack of qualified specialists. The child health care system created before the war in the whole USSR (Chuvashia included) and the medical and preventive work that was carried out during the war gave positive results. Child mortality decreased by 1.7 times compared to the pre-war 1940. Thus, children’s health care in Chuvashia withstood this difficult test and proved its efficacy during the Great Patriotic War.